Assessment of Psychological Depression among Edentulous Patients in Tiruchengode – A Cross-sectional Study - Jennifer Monisha Rajan; Girish R Shavi; Shankar Shanmugam; Senthilkumar Sennan; Lalithambigai Gunasekaran; Kavya Ganesh Kamaraj (Journal of Indian Association of Public Health Dentistry)
Introduction Depression and anxiety are two psychosocial illnesses that are mostly comorbid. The prevalence of psychosocial diseases is increasing worldwide. Both can affect general and oral and dental health, which can be physiological or behavioral. Aim The aim is to assess the Psychological Depression among edentulous patients in Tiruchengode. Settings and Design This was a cross-sectional study conducted in Tiruchengode. Materials and Methods The study was performed among 60 completely edentulous patients of Tiruchengode using the Patient Health Questionnaire for 5 months. Statistical Analysis Descriptive analysis was performed using SPSS Version 25. Results About 56.67% of patients were in the nonminimal group, 33.33% of them were in mild depression, and 10% were in moderate depression level. Conclusion Depressive symptoms were associated more with poor appetite and impaired chewing ability. Hence, more awareness and care should be given, particularly to older individuals with complete edentulism, which causes chewing disability.